Socio-Demographic Determinants of Emotional and Spousal Support During Pregnancy: A Comparative Study of Hukkeri and Khanapur Talukas - Shobha Sidnal; Manjula G.K, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Pregnancy is a critical period in a woman’s life, marked by profound physiological, psychological, and social changes. The quality of support received during this time—particularly emotional and spousal support—plays a pivotal role in shaping maternal health outcomes. This study employed a descriptive cross-sectional design to examine the socio-demographic determinants of emotional and spousal support among pregnant women in Hukkeri and Khanapur talukas of Karnataka. The present study focuses on Hukkeri and Khanapur talukas in Karnataka, two regions with distinct socio-cultural profiles. By examining the socio-demographic characteristics of women in these areas, the research aims to understand how factors such as age, religion, caste, education, occupation, income, and family type influence the support received during pregnancy. The study adopts a comparative approach, analyzing data from 80 respondents—40 from each taluka—to identify patterns and correlations that can inform targeted interventions. This study highlights the critical role of socio-demographic factors in shaping emotional and spousal support during pregnancy. The findings reveal that variables such as education, income, caste, and family structure significantly influence the quality and extent of support received by expectant mothers.
Keywords: Pregnancy; Emotional Support; Husband; Mother; Education; Toilet; Counselling